เทคโนโลยี สิทธิ และกฎหมาย: ฉากทัศน์ใหม่ของตำรวจไทย - กองทอง, พ.ต.อ.ชัยบัญชา (วารสาร มมร ยศสุนทรปริทรรศน์, 2025)
In the digital age, technological advancements have profoundly impacted all aspects of society, including law enforcement practices in Thailand. Digital technology not only enhances the efficiency of investigation, evidence collection, and public order maintenance, but also raises critical questions concerning civil rights and the role of law in balancing state authority with individual freedom. The integration of advanced tools such as intelligent surveillance cameras, facial recognition systems, artificial intelligence (AI), and big data analytics into policing operations represents a structural transformation that strengthens law enforcement precision and responsiveness. However, these technologies must be deployed within a clear legal framework and grounded in ethical principles, especially concerning the protection of personal data and privacy rights. One of the major issues facing Thai policing today is the inadequacy of existing legal provisions in addressing the challenges posed by new technologies. Current laws lack comprehensive regulations regarding the collection, processing, and use of personal data by state authorities, the role of AI in decision-making affecting individual rights, and transparency in the exercise of police powers. In this context, it is imperative to develop a specific legal framework for the use of digital technologies in law enforcement—one that ensures informed consent, data minimization, independent oversight, and public participation. This article advocates for a systematic establishment of legal and ethical guidelines for policing in the digital era. Core principles should include transparency, accountability, and a firm commitment to human rights. In doing so, technology will not merely serve as an instrument of state power, but as a force for justice in which the public can place its trust and confidence.